BIOTRANSFORMATION OF PVC FILMS BY LIQUID WASTE FROM LANDFILL - Martins-franchetti, S.m. [UNESP]; Silva, E.r.; Trombibni, R.c. (Instituto Biológico, 2025)
Most synthetic polymers, such as polyethylene (PE), polystyrene (PS) and poly (vinyl chloride) (PVC), cannot be metabolized by microorganisms. Their discard is problematic not only because of the big volume but also because they cause injuries and death to fish and birds. In the case of PVC, incineration produces a toxic gas, the recycling is limited to a few products such as flooring and laminated materiais and the biodegradation is difficult. The hydrophobic character of synthetic polymers prevents the microbial attack and the presence of additives, trace monomers, catalysts and solvents in PVC may alter some properties and further biodegradation. This process can be affected by a variety of environmental factors such as: oxygen, temperature, water, sunlight and pollutants. Changes in polymers take place slowly and the characterization of degradation is difficult. The physico-chemical and mechanical properties of polymers depend on the chemical structure and morphology of the polymer matrix. Polymer characterization can be made by microscopic and structural methods: scanning electron microscopy (SEM) and infrared spectroscopy (IR). The present work shows that thin films of PVC undergo microstructural and superficial modifications, when submitted to treatment with municipal liquid from waste (chorume), for 20 days at 32ºC.

A maioria dos polímeros sintéticos tais como polietileno (PE), poliestireno (PS) e cloreto de polivinila (PVC), não é assimilada por microrganismos. Seu descarte é problemático não só pelo grande volume acumulado na natureza, como pelo dano que pode causar à vida animal. No caso do PVC, a incineração produz um gás tóxico, a reciclagem é limitada a poucos produtos, tais como: forros e laminados e a biodegradação é difícil. O caráter hidrofóbico dos polímeros sintéticos evita o ataque microbiano e no PVC a presença de aditivos pode alterar algumas de suas propriedades e sua posterior biodegradação. Este processo pode ser afetado por um variedade de fatores ambientais, tais como: oxigênio, temperatura, água, luz do sol e poluentes. As mudanças nos polímeros ocorrem lentamente e sua caracterização é difícil. As propriedades físico-químicas e mecânicas dos polímeros dependem da estrutura química e da morfologia da matriz polimérica. Sua caracterização pode ser realizada através de métodos microscópicos e estruturais: microscopia eletrônica de varredura (MEV) e espectroscopia de absorção no infravermelho (IV). O presente trabalho mostra que filmes finos de PVC, sofrem modificações estruturais e superficiais significativas, quando submetidos a tratamento com resíduo líqüido extraído do lixão municipal (chorume), durante 20 dias a 32ºC.
BIOTRANSFORMAÇÃO DE FILMES DE PVC POR CHORUME PROVENIENTE DE ATERRO SANITÁRIO
Keywords: PVC films; biotransformation; infrared; scanning eletronic microscopy; waste; landfill.; Filmes de PVC; biotransformação; infravermelho; microscopia eletrônica de varredura; resíduo; aterro.